Sickle cell disease and pregnancy. Experience at the Institute of Hematology and Inmunology, Cuba. - Hernández Padrón, Carlos; del Loreto Téllez, Dra. María; Espinosa-Estrada, Edgardo; Ramón Rodríguez, Luis G; Avila Cabrera, Onel M; Pujadas Ríos, Xiomara; Agramonte Llanes, Olga (Revista Cubana de Hematología, Inmunología y Hemoterapia, 2012)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <mce:style><! st1\:*behavior:url(#ieooui) –> <!–[endif] –><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabla normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> Pregnancy in women with sickle cell disease (SCD) is a high-risk situation associated with increased incidence of maternal and fetal morbidity and mortality. In Cuba, the maternal care program includes the primary level and the gestational age at booking is before the 12 week of gestation and all deliveries are institutional. All pregnant women with SCD in La Habana are attended at the Institute of Hematology and Immunology (IHI) by a multidisciplinary team and labor takes place at the obstetrics service of the General Hospital next to the IHI. From January 2000 to December 2009, 68 pregnant women with SCD were attended in labor; the frequency of the visits is every two weeks from gestational age at booking until week 32 of pregnancy and weekly until week 36 when they are hospitalized, in week 38 induction of labor is made. Patients were hospitalized upon the appearance of any event and in such cases induction of labor was made in week 36, if fetus was mature. The fetal well-being was evaluated starting from week 28 and every two weeks until childbirth. Non prophylactic blood transfusion or prophylactic exchange transfusions were indicated as this depends on the criteria of attending team; only 16 patients presented alert signs of requiring blood transfusion, 4 requiring blood exchange transfusions. All these procedures were carried out in the third trimester of pregnancy; 47 patients required caesarea indicated by the obstetrician; 17 newborns were underweight but only one with low apgar score. Two fetal deaths occurred and one new born had early neonatal death. Only one maternal death was reported.